DEVELOPMENT OF THE BAKPIA 'MBAH WIRO 378' INDUSTRY THROUGH BUSINESS MODEL CANVAS AND BLUE OCEAN STRATEGY AT CLASS IIA YOGYAKARTA PRISON - Ziskind, Muhammad Hans; Rifani, Denny Nazaria (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to develop the business strategy of Bakpia 'Mbah Wiro 378' at Yogyakarta Class IIA Correctional Facility using the Business Model Canvas (BMC) and Blue Ocean Strategy (BOS) approaches. The research method used is descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation related to bakpia business operations in the Class IIA Correctional Facility. The BMC approach was used to analyze nine key business elements, while BOS was applied to identify new opportunities in untapped markets. The research results show that the application of BMC and BOS can provide effective strategies to improve product quality, production efficiency, and marketing. Additionally, these strategies help the 'Mbah Wiro 378' bakpia industry face competition with similar products in the local market, while also opening opportunities for expansion into wider markets. Keywords: Business Model Canvas; Blue Ocean Strategy; Business Strategy; Bakpia; Correctional Facility; Yogyakarta